2010
DOI: 10.1007/s10535-010-0136-6
|View full text |Cite
|
Sign up to set email alerts
|

In vitro regeneration of Solanum nigrum with enhanced solasodine production

Abstract: High frequency of shoot formation was achieved from Solanum nigrum L. leaves on Murashige and Skoog (MS) medium without any callusing stage. Shoot forming ability was more pronounced on leaves positioned dorsally. For shoot induction, 2.0 mg dm -3 benzylaminopurine and 1.5 mg dm -3 kinetin were observed to be the most effective plant growth regulators (PGRs). The present paper also describes first successful induction of in vitro flowering in S. nigrum. The leaf derived shoots were excised and treated with var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 24 publications
2
13
1
Order By: Relevance
“…The results are in agreement with earlier findings as observed in Sesamum indicum [28], Enicostema axillare [29], same as the concentration [30], whereas, the combination of 10 μM BAP plus 4 μM IAA increases the shoot induction and more number of shoots. The results also are in agreement with earlier findings as observed in Mentha viridis [31], Bacopa monneiri [32], Lobelia nicotianaefolia [33] and Solanum nigrum [34] where BAP and KIN resulted in marked increase in shoot multiplication.…”
Section: Phytochemical Analysis By Gc-mssupporting
confidence: 93%
See 1 more Smart Citation
“…The results are in agreement with earlier findings as observed in Sesamum indicum [28], Enicostema axillare [29], same as the concentration [30], whereas, the combination of 10 μM BAP plus 4 μM IAA increases the shoot induction and more number of shoots. The results also are in agreement with earlier findings as observed in Mentha viridis [31], Bacopa monneiri [32], Lobelia nicotianaefolia [33] and Solanum nigrum [34] where BAP and KIN resulted in marked increase in shoot multiplication.…”
Section: Phytochemical Analysis By Gc-mssupporting
confidence: 93%
“…The third compound was (E)-9-octadecenoic acid ethyl ester (C20H38O2) which was determined at the RT of 13.867 min and it has the molecular weight of 280 (table 2). This compound was absent in in vitro regenerated shoots of C. gynandra and it has the property of antimicrobial and antiinflammatory activity (table 3) [34][35][36]. 9,12,15-octadecatrienal is also one of the chemical constituents that were identified from plantlets.…”
Section: Phytochemical Analysis By Gc-msmentioning
confidence: 99%
“…Our results are in agreement with the previous report in which B5 medium produced more shoots as compared to MS and SH basal media in S. nigrum (Hassanein and Soltan, 2000). In contrast, Bhat et al (2010) achieved high regeneration potential of S. nigrum on MS medium. Similarly, Gaurav et al (2016) also reported the efficacy of MS than B5 basal media in shoot regeneration of Withania somnifera.…”
Section: Discussionmentioning
confidence: 75%
“…In the present study, IBA formed more number and longest roots on MS medium, whereas NAA produced fewer roots in B5 medium. Similarly, Bhat et al (2010) reported 100% rooting with 15.2 number and average root length of 4.5 cm at 0.25 mg/L IBA in S. nigrum. Our results are different from these reports in terms of early root induction and vigorous growth under the variable conditions.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation